Narrow-Band Imaging Colonoscopy to Assess Mucosal Angiogenesis in Ulcerative Colitis. (24th February 2019) - Guo, Tao; Qian, Jia-Ming; Yang, Ai-Ming; Li, Yue; Zhou, Wei-Xun
Abstract : Background and Aim . It has been documented that angiogenesis is a largely unstudied component of the pathogenesis of ulcerative colitis (UC). Under narrow-band imaging (NBI) colonoscopy, the mucosal vascular pattern (MVP) can be visualized without the use of dyes. The aim of this study was to assess the grade of mucosal angiogenesis based on the MVP in UC. Methods . A total of 119 colorectal segments taken from 42 patients with UC were observed using NBI colonoscopy. The MVP was classified as follows: clear, obscure, or absent. Quantification of the degree of inflammation was performed using histological colitis scoring. Potent angiogenic activity was assessed by immunohistochemical staining for vascular endothelial growth factor (VEGF). Microvascular density was assessed using vessel counts as revealed by CD31 staining. The correlation between the MVP and histological grades of inflammation and angiogenesis was evaluated. Results . The MVP correlated well with the histological severity of inflammation. We also demonstrated an increasing level of microvascular density and VEGF staining along with the ordered types of MVPs. In addition, a statistically strong association existed between microvascular density and VEGF staining. Conclusions . NBI colonoscopy might be a useful tool for the in vivo assessment of the grade of mucosal angiogenesis in UC.